Scientific production of Shahid Beheshti University of Medical Sciences in Scopus between 2011-2014 - HajiHashemi, Zahra; Malih, Narges; Vafaee, Reza; Sohrabi, Mohammad-Reza (Social Determinants of Health, 2016)
Background: Scientometric evaluations are important part of research assessment which can help universities to visualize the effect of their achievements and assess the effect of policy changes and investments in the field knowledge development. Current study aimed to evaluate the scientific production of the faculty members affiliated to Shahid Beheshti University of Medical Sciences in Scopus database between 2011- 2014. Methods: Faculty members of Shahid Beheshti University of Medical Sciences participated in this cross sectional study. We had the names and affiliation of all faculty members based on university’s Human Resources Management database. All the faculty members were recruited in the study. Total number of the articles, total article’s’ citations and H Index between 2011-2014 were used for evaluation of faculty members. Scopus online webpage was the source of extracting the indices. Results: there had been 1299 faculty members working at the university. Of all participants, 165 (12.7%) were professors, other academic degrees were associate professors 335 (25.8%), assistant professors 656 (50.5%), associate professors 335 (25.8%) and instructors 112 (8.7%)., respectively. The findings of current study showed that each faculty member was contributed in in a mean of 14 person- articles and there had been 95 citations to the articles in average. The mean H index for the university was 3.2 . Conclusion: Current study has illustrated a general image of the articles affiliated to Shahid Beheshti University of Medical Sciences which were indexed at Scopus database from 2011-2014. Results showed the universities scientific production had significant growth during these years.